Exceptional lithium diffusion through porous aromatic framework (PAF) interlayers delivers high capacity and long-life lithium–sulfur batteries. Issue 2 (20th December 2021) - Ghasemiestahbanati, Ehsan; Shehzad, Areeb; Konstas, Kristina; Setter, Caitlin J.; O'Dell, Luke A.; Shaibani, Mahdokht; Majumder, Mainak; Hill, Matthew R.
Abstract : Sulfonated porous aromatic frameworks (SPAFs) accelerate Li-ion diffusion while retarding the polysulfide shuttle effect in Li–S batteries. This leads to high residual capacity above 1000 mA h g −1 and coulombic efficiency (>99.5%) after 500 cycles. Abstract : Lithium–Sulfur (Li–S) batteries offer potential for significant energy density storage gains in concert with the use of sustainable electrode materials. Their cycling stability and slow charging kinetics need significant improvement for deployment in practical settings. Consequently, facilitated transport within the cell is critical for promoting lithium transport whilst simultaneously retarding the movement of polysulfides, which limit the capacity and stability. We have developed a nanoporous interlayer with an ideal pore architecture and surface chemistry that overcomes these challenges. Porous Aromatic Frameworks (PAFs) have uniform 13 Å pores and exceptional internal surface areas that can be readily chemically functionalized. Appropriate sulfonation levels (SPAF) within these pores can deliver exceptional lithium ion transport rates, concomitant with the repulsion of unwanted polysulfide moieties. This combination of properties leads to outstanding capacity retention, above 1000 mA h g −1 after 500 cycles at practical charge rates. Our high capacity and cyclable battery design is also supported by high coulombic efficiency (av. >99.5%) and sulfur utilization (∼96%) as well as excellent lithium anode protection. These remarkable properties have been methodically explored with a suite of analytical techniques that link the battery performance to the fundamental physicochemical properties of the SPAF hybrid interlayer.